Comparative Proteomics Reveals the Spoilage-Related Factors of Shewanella putrefaciens Under Refrigerated Condition - Yi, Zhengkai; Xie, Jing (Frontiers in Microbiology, 2021)
Shewanella putrefaciens is a microorganism with strong spoilage potential for aquatic products. This study aimed to investigate the potential spoilage factors of S. putrefaciens by comparative proteomic analysis. The spoilage potential of two strains of S. putrefaciens (00A and 00B) isolated from chilled spoiled bigeye tuna was investigated. The results of total volatile basic nitrogen (TVB-N), trimethylamine (TMA) in fish inoculated with S. putrefaciens, extracellular protease activity of S. putrefaciens, and degradation of fish proteins indicated that the spoilage potential of S. putrefaciens 00A was much higher than that of 00B. Fish proteins are usually degraded by spoilage microorganism proteases into small molecular peptides and amino acids, which are subsequently degraded into spoilage metabolites in bacterial cells, leading to deterioration of fish quality. Thus, proteomic analysis of the extracellular and intracellular proteins of 00A vs. 00B was performed. The results indicated that the intracellular differentially expressed protein (IDEP) contained 243 upregulated proteins and 308 downregulated proteins, while 78 upregulated proteins and 4 downregulated proteins were found in the extracellular differentially expressed protein (EDEP). GO annotation revealed that IDEP and EDEP were mainly involved in cellular and metabolic processes. KEGG annotation results showed that the upregulated proteins in IDEP were mainly involved in sulfur metabolism, amino acid metabolism, and aminoacyl-tRNA biosynthesis, while downregulated proteins were related to propanoate metabolism. In contrast, EDEP of KEGG annotation was mainly involved in ribosomes, quorum sensing, and carbohydrate metabolism. Proteins associated with spoilage containing sulfur metabolism (sulfite reductase, sulfate adenylyltransferase, adenylyl-sulfate kinase), amino acid metabolism (biosynthetic arginine decarboxylase, histidine ammonia-lyase), trimethylamine metabolism (trimethylamine-N-oxide reductase), and extracellular proteins (ATP-dependent Clp protease proteolytic subunit) were identified as upregulated. These proteins may play a key role in the spoilage potential of S. putrefaciens. These findings would contribute to the identification of key spoilage factors and understanding of the spoilage mechanism of microorganisms.